Art as the Manifestation of Embodiment in the Age of Modern technology - Ferdinand Indrajaya (Graduate School of Institut Seni Indonesia Yogyakarta, 2018)
It is undeniable that modern technology has been penetrating our contemporary life in myriad aspects. From the water we drink, foods we eat, to the installed applications inour phone. Hence modern technology has become one dominating worldview on itsown which skips our reflection upon it. Its rapid growth stems from the dismissal oftradition and simultaneously with the tremendous scientific discoveries with its inherentinstrumental rationality. It actively participates in serving the irrational dimension ofour cybernetics-contemporary life. Thus it is not a neutral ensemble of devices, butnormatively-prescriptive directs our being in achieving our goals mechanically. AsHeidegger said, it enframes our being in the world in a disembodied fashion. Enframing,is the quintessence of modern technology. Merleau-Ponty, as another ardent critic, alsostated that modern technology is essentially manipulative. Under the heading of scientism(and or cybernetics), it anesthetizes humanity as its own manipulandum. Contrastingwith such view, art potentially re-attunes our relation with things. From Merleau-Ponty’sphenomenological perspective, art (especially painting) powerfully shows the prereflectiveand embodied contact with the world. This paper is an attempt to show the roleofart in a life that has been eclipsed by the modern technological worldview.